2013
DOI: 10.1080/13676261.2013.780125
|View full text |Cite
|
Sign up to set email alerts
|

Young teenagers' experiences of domestic abuse

Abstract: This article reports on the first findings from the ESRC funded from Boys to Men Project. In total, 1143 pupils aged 13-14 years completed a questionnaire to assess their experiences of domestic abuse as victims, witnesses and perpetrators. Overall, 45% of pupils who had been in a dating relationship reported having been victimised, 25% having perpetrated it, with the only difference in rates of victimisation and perpetration between boys and girls being in relation to sexual victimisation. Of the whole sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 13 publications
5
50
2
Order By: Relevance
“…Forms of coercive control may also be present in the relationships of some young people (Barter et al, 2009;Wood et al, 2011). It remains unclear whether controlling behaviours identified in young relationships (for example constantly checking up on partners; placing restriction on who their partners see or communicate with) constitutes coercive control or rather reflects young people's unresolved struggles around trust and jealously (Barter et al 2009;Fox et al 2013). It is however possible that male partners are using the sexual images sent to them as a means of exerting power over their partners through the threat of sharing, or that sexual images are used by partners as a form of 'relational aggression' (Leadbeater et al, 2008) -to spread rumours to damage a young person's relationship with his/her peers.…”
Section: Association Between Ipva and Sextingmentioning
confidence: 99%
“…Forms of coercive control may also be present in the relationships of some young people (Barter et al, 2009;Wood et al, 2011). It remains unclear whether controlling behaviours identified in young relationships (for example constantly checking up on partners; placing restriction on who their partners see or communicate with) constitutes coercive control or rather reflects young people's unresolved struggles around trust and jealously (Barter et al 2009;Fox et al 2013). It is however possible that male partners are using the sexual images sent to them as a means of exerting power over their partners through the threat of sharing, or that sexual images are used by partners as a form of 'relational aggression' (Leadbeater et al, 2008) -to spread rumours to damage a young person's relationship with his/her peers.…”
Section: Association Between Ipva and Sextingmentioning
confidence: 99%
“…A recent study of 13 to 14 year olds in the UK (N ¼ 1143) found that 45% of pupils who had been in a dating relationship reported having experienced domestic abuse and 25% having perpetrated it (Fox et al 2013). There is, therefore, good reason to target preventive interventions at teenagers in early adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…The types of behavior that can be included in technology-assisted adolescent dating violence and abuse (TAADVA) have also been presented by the Domestic Violence Prevention Centre (DVPC; n.d.) to consist of coercion, threats, harassment, intimidation, emotional and verbal abuse, stealing online identity, controlling behaviors, sexual abuse, and cyber stalking. Research interest, however, has only recently begun to investigate the prevalence of TAADVA (e.g., Associated Press & MTV, 2009Barter et al, 2009;Cutbush, Ashley, Kan, Hampton, & Hall, 2010;Cutbush, Williams, Miller, Gibbs, & Clinton-Sherrod, 2012;Draucker & Martsolf, 2010;Fox et al, 2014;Hinduja & Patchin, 2011;Korchmaros, Ybarra, Langhinrichsen-Rohling, Boyd, & Lenhart, 2013;Picard, 2007;Tompson, Benz, & Agiesta, 2013;Zweig, Dank, Yahner, & Lachman, 2013), and only two of these studies were conducted in the United Kingdom (e.g., Barter et al, 2009;Fox et al, 2014). Two of these studies have used the CDC's definition of ADVA, which includes ECT as an avenue for abusive behavior (e.g., Cutbush et al, 2012;Tompson et al, 2013), while the others have used their own definitions of TAADVA.…”
Section: Introductionmentioning
confidence: 99%
“…These estimates are fairly comparable to those reported for psychological/emotional ADVA victimization (35%-55%) and instigation (20%-70%) in this earlier review (Stonard et al, 2014). Measures of TAADVA in these 12 studies typically include checking a partners messages without permission, checking the whereabouts of a partner, demanding passwords to online accounts, deleting or un-friending ex-partners, using information posted online against a partner, pressuring partners to engage in sexual acts, insults or put downs, spreading rumors about a partner on the Internet, threatening a partner via ECT, sharing private or embarrassing images or videos of a partner, making a partner feel afraid not to respond to contact, and restricting a partner's ECT use (Associated Press & MTV, 2009Barter et al, 2009;Cutbush et al, 2010;Cutbush et al, 2012;Draucker & Martsolf, 2010;Fox et al, 2014;Hinduja & Patchin, 2011;Korchmaros et al, 2013;Picard, 2007;Tompson et al, 2013;Zweig et al, 2013). Females have been reported to be more likely to report being a victim of both nonsexual and sexual TAADVA (e.g., Barter et al, 2009;Zweig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%